Peer Group Support Terhadap Self- Efficacy Pasien DM Tipe II - Dirgantari Pademme; Triani Banna (Jurnal Ilmiah Kesehatan (JIKA), 2021)
Diabetes Mellitus (DM) can cause serious damage to the heart, blood vessels, eyes, kidneys, nerves and even death. The prevalence of DM continues to increase. The risk of complications in DM patients can be reduced through good self-management, this is influenced by self-efficacy (SE). SE is the patient's belief in his ability to perform self- management behavior. The results showed that SE in DM patients was still lacking. The role of nurses is important in increasing SE in DM patients. The strategy that can be used is health education through a support group approach. The purpose of this study was to determine the effect of peer group support on the self-efficacy of Type II DM patients. This research is a quasi-experimental research with one group pre-test and post-test design. The population that meets the inclusion and exclusion criteria will be used as a sample for this study. Sampling in this study using purposive sampling technique. The data that has been collected will be processed and analyzed using the t-test if it is normally distributed, whereas if the data is not normally distributed, the test used is the Wilcoxon sign-rank test. The results of the Wilcoxon signed ranks test obtained a p-value of 0.000 (? = 0.05), so it can be concluded that peer group support has an effect on SE in DM patients.